Transformasi Kerajinan Tradisional Serta Penerapan Teknologi Anti-UV pada Kain Tenun Troso untuk Pasar Modern - Muhammad Syaroni; Orieza Maula Saputri; Kharis Fadlullah Hana (Journal of Economics and Business Research (JUEBIR), 2025)
This research aims to develop the innovation of Troso woven fabric products as a local cultural heritage by applying anti-ultraviolet (anti-UV) technology to increase added value and competitiveness in the modern market. The method used is Research and Development (R&D) which consists of problem identification stages, literature studies, field observations, to design and prototyping. Troso woven fabrics, which have the power of high aesthetic and cultural value, have the potential to be developed through environmentally friendly technological approaches, one of which is by coating titanium dioxide (TiO₂) and zinc oxide (ZnO) nanoparticles to provide protection against UV radiation. The results of this development show that the incorporation of functional technology with traditional values can create textile products that are not only aesthetically pleasing, but also adaptive to the needs of modern consumers, particularly in the outdoor and active fashion sectors. This research is expected to make a real contribution to the preservation of local culture based on innovation and become a reference for the sustainable development of other traditional handicraft products